MODELLING THE INTERACTIONS BETWEEN SOIL SURFACE PROPERTIES AND WATER EROSION - Kirkby M. (My University, 2002)
Interactions between soil surface properties, water runoff and erosion occur at many time and space scales. The paper focuses primarily on the effects of soil microtopography at a range of spatial scales and considers some new conceptual approaches to modelling its effect on runoff generation, flow concentration and sediment transport. In this paper, the local generation of runoff is considered through the simplifying concept of a discrete runoff threshold. The effect of random roughness is considered independently in the down-slope and cross-slope directions. Roughness elements measured in the cross-slope direction concentrate the flow within depressions, and create greater total sediment transport. Roughness measured in the down-slope direction represents elements which pond or impede the flow, reducing mean flow velocity and reducing sediment transport. This two-component approach to roughness provides a reasonable approximation to behaviour on fractally generated two-dimensional surfaces. If the roughness elements are assumed to be normally distributed, and independently random in the two directions, then explicit integrations can be made over the distributions, providing significant corrections to the relationship between mean flow depth and sediments transporting capacity.A second conceptual model is presented, exploring the implications of spatially random variations in surface flux capacity (storm total infiltration), surface (depression) storage and storm rainfall totals. It is demonstrated that some at-a-point runoff may, in principle, be generated, even where surface capacity appears to greatly exceed storm rainfall. In conclusion, it is argued that these effects, together with others not covered here, should be included in the next generation of soil erosion models.
Keywords: WATER EROSION; MODELLING; TIME AND SPACE SCALES; VERTICAL AND LATERAL SOIL VARIATIONS